(untitled) (Journal of Biomedical Investigation, 2023)
Background of the study: Exposure to HAART regimen especially Azidothymidine (AZT) therapy has neurotoxic adverse effects like neuroinflammation. Aim: We assessed the role of Phenol extract of P.guineense leaf and antioxidants on the Azidothymidine challenge. Material and Methods: Thirty-six adult Wistar rats were randomized into nine groups of 4 rats each. Azidothymidine (AZT) was administered to all groups except the control which received 0.1mL saline. Others received 100 mg/kg of AZT for 8 days, 100 mg/kg of AZT+100 mg/kg of P.guineense, 100 mg/kg of AZT+ 200 mg/kg of P.guineense, 100 mg/kg of AZT + 400 mg/kg of P.guineense, 100 mg/kg of AZT+ Zinc, 100 mg/kg of AZT+ 3mg/kg of Melatonin, 100 mg/kg of AZT+ 1000mg/kg Cellgivity, and 100 mg/kg of AZT+ 50 mg/kg of Selenium for 14 days respectively. Cerebellar amoeboid microglia expression was by identified by CD68 marker. Result: AZT induces reactive microgliosis, and the P.guineense extract exhibited dose-dependent pleiotropic microglia retraction. The antioxidants: Zinc, melatonin, selenium and cellgevity deferentially mitigate the AZT effect by providing neuroprotection. The high dose of P.guineense, selenium, and cellgevity had a pronounced reversal effect on the microglia. Conclusion: The effective dose of phenol extract P.guineense was beneficial in halting the neuroinflammatory effect of AZT in the cerebellum.